Implementation of Independent Curriculum in the Subject of Al-Qur'an Hadith at MTsN 1 Baubau - Astuti, Sri; Jusu, La; Basri, Basri (Journal of English Language and Education, 2025)
This study explores the implementation of the Independent Curriculum in learning the Al-Qur'an Hadith subject at MTsN 1 Baubau. The Independent Curriculum, launched by the Minister of Education, aims to create an innovative learning atmosphere and empower students and teachers to think critically and creatively. The research method used is qualitative with an inductive approach, involving observation, interviews, and documentation. The results of the study indicate that although there are still challenges in implementation, such as the dominance of old methods in teaching, the Independent Curriculum provides opportunities to improve the quality of learning through a more flexible approach, character development, and the use of innovative learning methods. This study emphasizes the importance of careful planning, varied implementation, and ongoing evaluation to achieve relevant and meaningful educational goals.